Pemeriksaan Kesehatan pada Kucing di Wilayah Sekitar Field Research Center Kulon Progo, Yogyakarta - Lestari, Fajar Budi; Prihanani, Nur Ika; Tjahajati, Ida; Syazwina, Alvina Meita; Latifah, Khilda Tsania; Fatiha, Azzahra Jasmine; Wahyuningtyas, Helfi (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Health disorders in companion animals are commonly encountered and may result from bacterial, viral, or fungal infections, as well as parasitic infestations. Cats (Felis catus) are among the domestic animals most closely associated with humans. This study aimed to evaluate the health status and identify diseases in cats inhabiting the area surrounding the Field Research Center (FRC), Yogyakarta. A total of 27 cats from the FRC area were included in this study. Fecal samples, ear swabs, skin scrapings, and blood samples were collected for laboratory examination. Fecal samples were analyzed using the native method to detect gastrointestinal parasites, ear swabs were examined for the presence of ear mites, skin scrapings were used to identify ectoparasites, and blood samples were analyzed using a hematology analyzer. Based on physical and laboratory examinations, cats in the FRC area were affected by parasitic infestations (scabies, ear mites, and pediculosis) and bacterial infections (rhinitis, conjunctivitis, enteritis, and otitis). Routine health examinations are essential for disease prevention and the improvement of animal welfare.